Use of remote consultations among frequent and non-frequent users of general practitioner consultations. A population-based registry study - Eli Kristiansen; Bjarne Austad; Trine Strand Bergmo; Børge Lønnebakke Norberg; Gunnhild Åberge Vie; Paolo Zanaboni (BMC Health Services Research, 2026)
Abstract Background A significant part of general practitioner (GP) consultations is conducted remotely through text-based, video or telephone consultations. While we know that the use of remote consultations varies by patient demographics, little is known about how patients with different needs for GP consultations use remote consultations. This study examines the use of remote consultations among frequent (≥ 10 remote and/or physical consultations) and non-frequent (< 10 remote and/or physical consultations) users of GP consultations, and their use of remote consultations across diagnoses. Method Retrospective population-based registry study of all GP consultations conducted in Norway in 2023. Descriptive statistics are presented. Results In 2023, 21% (3,595,577/16,897,833) of all GP consultations were conducted remotely. Frequent users, who represented 9% of patients, had a mean proportion of remote consultations over total consultations (both remote and physical consultations) of 29%. Non-frequent users accounted for 91% of the patients; their mean proportion of remote consultations was 14%, and 69% of them did not have any remote consultations at all. Higher proportions of remote consultations were observed among patients living in larger municipalities and among those who received several sick leaves. A lower proportion of remote consultations was observed among patients who had seen more than one GP during the year. These trends were stronger among frequent users. Remote consultations were used for most diagnoses. Frequent users had more remote consultations for musculoskeletal and psychological conditions, whereas respiratory diagnoses were more prevalent in remote consultations among non-frequent users. Remote consultations seemed less utilised for diagnoses where a physical examination is often required. Conclusion This study highlights differences in the use of remote consultations between frequent and non-frequent users, where frequent users had a higher proportion of remote consultations. The study cannot answer whether the difference in use is related to need, patient preferences or disparities in access to remote consultations. Remote consultations are widely used across diagnoses, particularly for respiratory, musculoskeletal, and psychological conditions, indicating good integration into general practice. Future research should investigate whether the quality and effectiveness of remote consultations are comparable to physical consultations.